"Assessment Research for the Benefit of Humanity": An Interview with Randy Thrasher and Yoshinori Watanabe. Issue 3 (27th May 2022) - Kubota, Keisuke; Yokouchi, Yuichiro; Koizumi, Rie
ABSTRACT: This is an interview article with Randolph H. Thrasher and Yoshinori Watanabe, leading experts on language assessment in Japan. Randolph H. Thrasher is professor emeritus at Okinawa Christian University, Japan, and International Christian University, Japan. He has made numerous significant contributions to spreading and supporting the field of language assessment. Yoshinori Watanabe is a professor at Sophia University, Graduate School of Language and Linguistics, Japan. He is also a renowned figure in language assessment and testing domestically and internationally. We interviewed them to deepen insights into various aspects of language assessment in Japan, as well as in the world. This interview was conducted in March 2021 via e-mail because of the global COVID-19 pandemic. In answering our questions for this interview, Professor Thrasher and Watanabe wrote about their own early lives and careers and their fruitful experiences with Japan Language Testing Association (JLTA), shared their passionate beliefs about language assessment and testing from domestic and international perspectives, and offered hopeful messages to young researchers. 本稿は, 日本における言語テスティング分野を開拓し, 国際的にも活躍するRandolph H. Thrasher名誉教授 (沖縄キリスト教学院大学 国際基督教大学) と渡部良典教授 (上智大学大学院) へのインタビュー記事である。Thrasher名誉教授は第2代の, 渡部教授は現在, 第4代の日本言語テスト学会 (JLTA) 会長として学会を牽引している。両名は, 言語テスティング分野の学術的発展への貢献のみにとどまらず, 得られた研究成果を社会に還元し, 国際社会の外国語教育発展に貢献してきた, まさに日本を代表する言語テスティング研究者と言える。JLTA発足時からのメンバーである両名は, その中心として, 国際言語テスト学会 (ILTA) における活動をはじめ, 国際的にも長年活躍されている。その両名から, これまでのキャリア, JLTAでの貴重な経験, 国内および国際的な観点からの言語テスティングへの知見, 言語テスティングに対する情熱と信念, そしてこれからの言語テスティングの分野を担う若手研究者に対するメッセージをいただいた。